Atención al cliente en el Taller de Fabricación de Soldadura “freddy” de la ciudad de Babahoyo, en el periodo 2023. - Elizondo Tacle, Scarleth Elizabeth (2024)
The objective of this research is to determine the quality of customer service at the "FREDDY" workshop to provide good customer service. Therefore, to carry out this research, the mixed methodology was implemented in its documentary design, since a review was carried out. bibliographical reference to customer service and purchase satisfaction, because it constitutes an essential element when selling a product or service, since the level or degree of customer satisfaction will depend on this. For which a qualitative and quantitative approach was worked, where there were contributions from a strategic sector of the town, the clients of the FREDDY Welding Workshop. In addition, alternatives were sought to counteract the problem of poor attention received by employees, so we worked with workshops aimed at cooperative work, using three factors as a means: administrative, strategic, evaluation, and verification; Each one of them offers the necessary means to successfully complete this work.